2016
DOI: 10.1186/s12859-016-1394-x
|View full text |Cite
|
Sign up to set email alerts
|

STON: exploring biological pathways using the SBGN standard and graph databases

Abstract: BackgroundWhen modeling in Systems Biology and Systems Medicine, the data is often extensive, complex and heterogeneous. Graphs are a natural way of representing biological networks. Graph databases enable efficient storage and processing of the encoded biological relationships. They furthermore support queries on the structure of biological networks.ResultsWe present the Java-based framework STON (SBGN TO Neo4j). STON imports and translates metabolic, signalling and gene regulatory pathways represented in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…Some software tools already visualize element alignments between models as network graphs (e.g. BudHat [ 53 ], SemanticSBML, STON [ 61 ]), or present ranking scores for retrieved models (e.g. MASYMOS [ 45 ], SemanticSBML).…”
Section: Discussionmentioning
confidence: 99%
“…Some software tools already visualize element alignments between models as network graphs (e.g. BudHat [ 53 ], SemanticSBML, STON [ 61 ]), or present ranking scores for retrieved models (e.g. MASYMOS [ 45 ], SemanticSBML).…”
Section: Discussionmentioning
confidence: 99%
“…In [ 9 ] the authors explored the potential of using a graph database to facilitate data management and analysis to provide biological context to disease-related genes and proteins. Toure et al developed a Java-based framework that transforms biological pathways represented in SBGN format into the Neo4j graph database, enabling more powerful management and querying of complex biological networks [ 10 ]. Balaur et al demonstrated that advanced exploration of highly connected and comprehensive genome-scale metabolic reconstructions can benefit from an integrated graph representation of the model and associated data [ 11 ].…”
Section: Design and Implementationmentioning
confidence: 99%
“…Annotations have contributed to the successful reuse and exploration of models and data in tasks such as comparison 27,28 , interpretation 29 , retrieval [30][31][32] , integration [33][34][35][36][37] , simulation 38 , translation between formats 29,37,[39][40][41][42] (see also http://sbfc.sourceforge.net/mediawiki/index.php/SBML2BioPAX), and visualization 37,[43][44][45] . Semantic annotations are also a key component for model-driven design of synthetic biological systems where they are used in model composition tasks when constructing optimum biological systems built from models 41,[45][46][47][48] .…”
Section: Semantic Annotations and Their Utilitymentioning
confidence: 99%